Factors associated with smoking cessation success in Lebanon - Bacha ZA; Layoun N; Khayat G; Hallit S. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective: The objective is to assess factors associated with the success rate of smoking cessation among Lebanese smokers in a smoking cessation center. Methods: A cross-sectional data study, conducted between March 2014 and March 2016 in an outpatient smoking cessation center with 156 enrolled patients. The patient's nicotine dependence and motivation to quit smoking were evaluated according to the Fagerstrom Test for Nicotine Dependence and Richmond tests respectively. Results: The number of packs smoked per year decreased the odds of smoking cessation success (p=0.004, ORa=0.982, CI 0.97-0.994), while the compliance with the offered treatment increased the odds of success by 7.68 times (p<0.001, ORa=7.68, CI 3.438-17.187). Highly dependent and highly motivated smokers had more success in the quitting process compared to those with a lower dependence and motivation respectively. Conclusion: Our findings showed that many factors can influence smoking cessation, an experience described as difficult, most significantly the number of packs per year and compliance with the smoking cessation treatment. Moreover, although these outcomes are not representative of the entire Lebanese population, we believe that health authorities could utilize these results when implementing upcoming smoking cessations programs. All attempts at cessation should have a goal of reducing the number of packs smoked per year to improve the chances of ceasing into the future.